2022
DOI: 10.1139/cjpp-2021-0007
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine attenuates renal ischemia-reperfusion-induced liver damage: implication of TLR4/NF-κB, TGF-β, and BAX and Bcl-2 gene expression

Abstract: Ischemia-reperfusion injury (IRI) is typically associated with a vigorous inflammatory and oxidative stress response to hypoxia and reperfusion that disturbs the function of the organ. The remote effects of renal IRI on the liver, however, require further study. Renal damage associated with liver disease is a common clinical problem. Colchicine, a polymerization inhibitor of microtubules, has been used as an anti-inflammatory and anti-fibrotic drug for liver diseases. The goal of the current study was to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In the current study, we selected four ABC transporter genes (Abcc2, Abcc5, Abcf2, and Abcg2) based on a literature search. All these ABC trans- porter gene are expressed in the liver and in many processes in the liver such as inflammatory response and oxidative stress (39,40). In a previous IR study on the mouse liver, Ab-cg2 and Abcc2 gene levels were decreased seven days after liver ischemia (22).…”
Section: Discussionmentioning
confidence: 98%
“…In the current study, we selected four ABC transporter genes (Abcc2, Abcc5, Abcf2, and Abcg2) based on a literature search. All these ABC trans- porter gene are expressed in the liver and in many processes in the liver such as inflammatory response and oxidative stress (39,40). In a previous IR study on the mouse liver, Ab-cg2 and Abcc2 gene levels were decreased seven days after liver ischemia (22).…”
Section: Discussionmentioning
confidence: 98%
“…This result elucidates that ramelteon alleviates IRI by mitigating the inflammatory response. TLR4 is involved in the pathophysiology of inflammation and AKI induced by renal IRI ( 36 ). Yang et al showed that MT promotes autophagy and ameliorates renal IRI though TLR4/MyD88/MEK/ERK/mTORC1 ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Colchicine gel was reported to inhibit myocardial apoptosis and fibrosis in mice with myocardial infarction and improved cardiac function and structure ( Chen et al, 2020 ). Colchicine exerts its anti-inflammatory, anti-apoptotic and anti-fibrotic effects through upregulated hepatic B-cell lymphoma 2 (Bcl-2) and downregulated Bcl-2 associated X protein (BAX) expression and transforming growth factor-β (TGF-β) content, which attenuates rat liver injury induced by renal ischemia-reperfusion injury ( Awad et al, 2022 ). It was shown that when cytochrome C is released from mitochondria, it activates the caspase-3 apoptotic pathway and promotes cardiomyocyte apoptosis, making cardiac function impaired ( Radhakrishnan et al, 2007 ).…”
Section: Discussionmentioning
confidence: 99%